2021
DOI: 10.2478/sbe-2021-0002
|View full text |Cite
|
Sign up to set email alerts
|

Current Account Balance in Emerging Asia

Abstract: The current account balance is an important indicator which reveals information on a country’s economic situation such as investments, capital flows, and indebtedness. The main purpose of this study is to examine the current account balance conditions in emerging Asian countries. In this respect, the long-run and causality relationship between current account balance, economic growth, government expenditure, real interest rates, and foreign direct investment was examined. The panel data analysis was applied us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…Furthermore, the exchange rate appreciation rapidly increases exports compared to imports, resulting in a surplus balance of payments. This is in line with [25], [36], [39], which found that foreign direct investment negatively affects the current account balance.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…Furthermore, the exchange rate appreciation rapidly increases exports compared to imports, resulting in a surplus balance of payments. This is in line with [25], [36], [39], which found that foreign direct investment negatively affects the current account balance.…”
Section: Resultssupporting
confidence: 85%
“…FDI inflows have a favorable impact on the balance of payments due to the appreciation of the country's currency exchange rates. [36], [39] showed that foreign direct investment significantly affects the CA balance. Similarly, found that FDI had a significant positive effect on the CA balance.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…With the presence of foreign capital, a country can increase the output of export-oriented industries and reduce the volume of imports. Research results byBedir & Soydan (2016) and alsoHalil et al (2021) obtained Foreign Investment (FDI), which has a major impact on the current account balance. As forAriyani et al (2018), attracting direct investment (FDI) harms the current account balance.…”
mentioning
confidence: 99%